Statistics for the Behavioral Sciences - Heinzen Thomas E; Nolan Suzan A (Worth Publishers, 2008)
Preface, An Introduction to Statistics and Research Design: The Basic Elements of Statistical Reasoning, Descriptive Statistics: Organizing and Summarizing and Graphing Individual Variables, Visual Displays of Data: Graphs That Tell a Story, Probabilities and Research: The Risks and Rewards of Scientific Sampling, Correlation: Quantifying the Relation Between Two Variables, Regression: Tools for Predicting Behavior, Inferential Statistics: The Surprising Story of the Normal Curve, Hypothesis Testing with z Tests: Making Meaningful Comparisons, Hypothesis Testing with t Tests: Comparing Two Groups, Hypothesis Testing with One-Way ANOVA: Comparing Three or More Groups, Two-Way ANOVA: Understanding Interactions, Beyond Hypothesis Testing: Confidence Intervals and Effect Size and Power, Chi-Square: Expectations Versus Observations, Beyond Chi-Square: Nonparametric Tests with Ordinal Data, Choosing a Statistical Test and Reporting the Results: The Process of Statistics, Appendices, Index.